Mangrove Plantations in Goa - Kumar, Rajiv (Indian Forester, 1995)
Due to the degradation of mangrove forests in Goa in the past mainly do to biotic interference, the Forest Department of Goa has started planting mangrove species in the degraded areas to restore these forests to their pristine glory. The plantations raised so far can be graded as very Successful on the basis of overall results and are playing crucial role in the improvement of mangrove ecosystem in Goa. Our endeavour is to have a sound mangrove ecosystem primarily by adopting afforestation and conservation activities.